1998
DOI: 10.1159/000017981
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin: Does It Have a Role in the Pathogenesis of Psoriasis?

Abstract: Background: The aetiopathogenesis of psoriasis is still not fully understood. Recently, it has been reported that prolactin (PRL) exerts a proliferative effect on human keratinocytes in vitro. PRL may, therefore, play an important role in the pathogenesis of psoriasis. Objective: To assess the serum PRL level in patients with psoriasis vulgaris (PV). Methods: Serum levels of PRL were estimated in 12 patients with PV (age: 11–45 years with mean ± SD 30.4 ± 10.2 years; sex: 7 males, 5 females) and the results we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
33
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 12 publications
5
33
0
Order By: Relevance
“…Gorpelioglu et al and Priestley et al did not find any association between serum PRL levels and psoriasis as well as its activity (Gorpelioglu et al, 2008;Priestley et al, 1984). In contrast, a number of investigators have found a significant association between serum PRL and disease activity (Giasuddin et al, 1998;Dilmé-Carreras et al, 2011;Sanch, 2000).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Gorpelioglu et al and Priestley et al did not find any association between serum PRL levels and psoriasis as well as its activity (Gorpelioglu et al, 2008;Priestley et al, 1984). In contrast, a number of investigators have found a significant association between serum PRL and disease activity (Giasuddin et al, 1998;Dilmé-Carreras et al, 2011;Sanch, 2000).…”
Section: Discussionmentioning
confidence: 94%
“…However, there are scarce reports in the literature regarding the significance of PRL in alopecia areata and vitiligo (Gö nül, 2009;. Although many studies found increased serum PRL in patients with psoriasis (Giasuddin et al, 1998;Dilmé-Carreras et al, 2011), there is controversy, however, as to whether raised PRL levels are associated with disease activity. Gorpelioglu et al and Priestley et al did not find any association between serum PRL levels and psoriasis as well as its activity (Gorpelioglu et al, 2008;Priestley et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier small studies with 12 PV patients and 7 with PsA showed elevated serum PRL levels in PV (ref. 29 ) but not in PsA (ref. 30 ).…”
Section: Discussionmentioning
confidence: 97%
“…In another, independent patient group we have confirmed similar plasma PRL levels in 22 active RA patients compared to 16 healthy controls (44). In contrast, higher PRL levels have been reported in patients with psoriasis compared to control disease and healthy controls (45), and it has been suggested that PRL may play a role in the pathogenesis of psoriasis (46). Collectively, most of the evidence suggests that plasma PRL levels are on average not elevated in RA, while more validation is needed in conditions like psoriasis.…”
Section: The Role Of Prl In Ra and Psamentioning
confidence: 98%